2014
DOI: 10.1016/j.ijgo.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of confounding factors interfering with sexual function in women with minimal pelvic organ prolapse

Abstract: Sexual dysfunction is highly prevalent in women with minimal POP. Overactive bladder and low income are the major factors adversely affecting sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(29 reference statements)
0
2
2
Order By: Relevance
“…16 Karabulut et al demonstrated higher FSFI scores in women with POP with a longer total vaginal length. 17 However, in the present study, SF was not associated with POP stage or with POP-Q points. These results are consistent with the findings of Lowenstein et al who reported that SF was not correlated with prolapse of the different vaginal compartments, but was correlated with more bothersome POP.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…16 Karabulut et al demonstrated higher FSFI scores in women with POP with a longer total vaginal length. 17 However, in the present study, SF was not associated with POP stage or with POP-Q points. These results are consistent with the findings of Lowenstein et al who reported that SF was not correlated with prolapse of the different vaginal compartments, but was correlated with more bothersome POP.…”
Section: Discussioncontrasting
confidence: 76%
“…Yang et al found that lower Ba and C points of the POP‐Q system correlated with lower PISQ scores in women with SUI . Karabulut et al demonstrated higher FSFI scores in women with POP with a longer total vaginal length . However, in the present study, SF was not associated with POP stage or with POP‐Q points.…”
Section: Discussioncontrasting
confidence: 65%
“…Sexual function was not related to minimal anatomical POP [27]. However, women with more severe anatomical POP reported worse sexual function than healthy women [28].…”
Section: Sexual Functionmentioning
confidence: 75%
“…Symptoms may be far-reaching such as prolapse symptoms, voiding difficulties or pelvic floor pain [1]. Furthermore, sexual dysfunction can be an accompanying symptom with subsequent worse POP-related quality of life [2].…”
Section: Introductionmentioning
confidence: 99%